CONSTRUSTIVISTIC BIOLOGY INSTRUCTIONAL MODEL ICT-BASED (CBIM-ICT-BASED) FOR JUNIOR HIGH SCHOOL STUDENTS - ., adnan (Program Pascasarjana Universitas Negeri Makassar, 2015)
ABSTRACTThis research aimsÂ to develop a model of ICT-based contrustivistic biology learning (CBL-based ICT) for Junior High School students were valid. The problem posed is